Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis Matematika Siswa SMP - Nurlaeli, Nurlaeli (Lembaga Yasin AlSys, 2022)
The study aims to describe the effect of the problem based learning model towards students' mathematic critical thinking in Junior High School. This research is a quasi-experimental research with nonequivalent pretest-posttest kontrol group design. The sample in this study was 72 students of SMP Negeri 6 Mataram (experimental group = 36 students, kontrol group = 36 students) with sampling using random sampling technique. The research instruments used a description test consist of 5 questions. The results of students' msthematic critical thinking skills were measured based on the results of the posttest using a statistical test, namely the t-test using the 2016 Microsoft Excel application. The results of the t-test on students' mathematic critical thinking skills in the experimental group and the kontrol group. Viewable Results t-calc. = 2,980 t table= 1.944 so that t calc>t table it can be concluded that there is an effect of the problem based learning model on students' mathematic critical thinking skills.